Enzymatic activity as a popular parameter used to determine the quality of the soil environment - Furtak, Karolina; Gałązka, Anna (Polish Journal of Agronomy, 2019)
In the soil environment, there are many enzymeswhose origin is related to microorganisms. Enzymes participatein the synthesis of proteins and nucleic acids, they are also elementsof the carbon, nitrogen and phosphorus cycles. They alsoplay a role in less known cycles, such as the sulphur cycle orcellulose decomposition. Determination of soil enzymes activityis very popular in microbiology, biochemistry and agriculturalsciences. Their activity may be a measure of soil fertility. Thepresent report describes the importance of selected soil enzymesand the methods of their determination. However, it is importantto remember that a single enzyme cannot be an indicator of theenvironment. The enzymatic activity is sensitive to many naturaland anthropogenic factors affecting soil microorganisms. Onlycomprehensive researchers on the activity of many, different enzymescan provide reliable information on the state of the soilenvironment.